Subclinical hypothyroidism in children and adolescents after hematopoietic stem cells transplantation without irradiation - Milenković Tatjana; Vujić Dragana; Vuković Rade; Zečević Željko; Soldatović Ivan; Mitrović Katarina; Todorović Slađana; Zdravković Dragan (Vojnosanitetski Pregled)
Background/Aim. Although total body irradiation (TBI) was considered to be the primary cause of thyroid dysfunction following hematopoietic stem cells transplantation (HSCT), a significant prevalence of subclinical hypothyroidism after HSCT with chemotherapy-only conditioning regimens has been observed in several studies. The aim of this study was to assess changes in thyroid stimulating hormone (TSH) levels in children after HSCT, without the use of irradiation at any time in the course of the treatment. Methods. Our cohort consisted of 41 children and adolescents who underwent autologous or allogeneic HSCT and were available for follow-up for at least one year after transplantation. Irradiation was not performed in any of the subjects, neither during pretransplatation therapy, nor during conditioning. The median duration of follow-up was 2.9 years. The indications for HSCT were hematologic malignancy (41.5%), solid malignant tumor (34.1%), and other disorders (24.4%). The thyroid status of all the subjects was assessed prior to HSCT and after follow-up period. Results. Thyroid dysfunction after HSCT was present in 27 (65.8%) subjects. Subclinical hypothyroidism was the most common abnormality, presenting in 23 (56.1%) patients, primary hypothyroidism was present in one (2.4%) patient, while 3 (7.3%) subjects had low free T4 with normal TSH values. Significantly (p < 0.01) higher elevations in TSH levels were present in the patients who received chemotherapy for the underlying disease prior to HSCT. Conclusion. Our findings emphasize the need for long-term monitoring of thyroid function following HSCT, regardless of whether or not irradiation was used.